Numerical and Experimental Analysis of Copper Electroforming on an Aluminum Substrate as a Rotating Cone Electrode Cell. Issue 40 (25th October 2019) - Memannavaz, Hossein; Pebdeni, Hamid H.; Liaghat, Gholmhossein; Rahmati, Sadegh; Najafi, Mohammad; Fazeli, Hamid
Abstract: In this paper, the advantages of numerical simulation to improve the process of copper electroforming are demonstrated. In this regard, the finite element model of copper electroforming for a rotating cone electrode was first prepared and then, the effect of the key parameters, such as applied current density, solution conductivity, electrode spacing, and anode height, on the uniformity of the thickness was investigated. The model combines tertiary current distribution with Bulter–Volmer electrode kinetics and computational fluid dynamics at the turbulent condition. In order to validate the model, a cone‐shaped shell was produced by electroforming method in the laboratory. The obtained results illustrate that the tertiary current distribution model on the rotating cone cell cathode is accurate and efficient for the electroforming process simulation and it can be used for parametric studies. Moreover, the effect of the current density on the morphology and properties of the electroformed layer was investigated. Abstract : In this study, for the first time, the numerical method has been used so as to improve the electroforming process and to produce a conical shaped charge liner with a desirable microstructure and high uniformity. So in this research, the effects of different parameters on thickness uniformity of copper electroforming process were investigated. Tertiary current distribution combined with computational fluid dynamic (CFD) was used to model the electroforming process.